2018
DOI: 10.1007/s10853-018-2785-3
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-controlled morphology of bismuth sulfide for supercapacitor applications

Abstract: In our study, we report a facile solvothermal method for the synthesis of Bi 2 S 3 nanoparticles with unique morphologies using water and mixed solvent systems, such as ethylene glycol/water (1:1, v/v) and butyldiglycol/water (1:1, v/v). Altering the solution mixtures used in the solvothermal synthesis allowed the shape of the Bi 2 S 3 nanoparticles to be controlled. The synthesis of Bi 2 S 3 in water at 150°C for 24 h led to the formation of sphere-like particles 100-300 nm in size. Very uniform spherical nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 54 publications
(100 reference statements)
0
28
0
Order By: Relevance
“…These observations confirmed that with the change in the amount of EG in the mixed solvent, the morphology of the Fe 3 S 4 also changed and the sheet‐like structure started to form at higher EG : H 2 O ratio. The EG acted as complexing agent and thereby controlled the morphology of the hydrothermal product …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations confirmed that with the change in the amount of EG in the mixed solvent, the morphology of the Fe 3 S 4 also changed and the sheet‐like structure started to form at higher EG : H 2 O ratio. The EG acted as complexing agent and thereby controlled the morphology of the hydrothermal product …”
Section: Resultsmentioning
confidence: 99%
“…The EG acted as complexing agent and thereby controlled the morphology of the hydrothermal product. [24] HR-TEM images of FS 60 and FS 80 were acquired to investigate micro-structural features of these materials. The formation of sheet-like structures was confirmed from the HR-TEM images as shown in Figure 5a-b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvothermal/hydrothermal route is one of the popular synthesis methods because of high yield, facile, and low temperature . Moreover, it allows better control on the overall morphology of the final product via variation of the process parameters, such as nature of the solvent and/or surfactant, reaction temperature, and synthesis duration …”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Moreover, it allows better control on the overall morphology of the final product via variation of the process parameters, such as nature of the solvent and/or surfactant, reaction temperature, and synthesis duration. [35][36][37][38] Recently, our group has investigated FE characteristics of pristine Bi 2 S 3 and Bi 2 S 3 -CdS heterostructures, synthesized via a single-step hydrothermal route. [39] Furthermore, the FE behavior of various rGO-based heterostructures, such as rGO-WS 2 , [40] rGO-MoS 2 , [41] rGO-MnO 2 , [42] and rGO-TiO 2 , [43] has been investigated.…”
Section: Introductionmentioning
confidence: 99%